2021
DOI: 10.1136/bmjopen-2020-042297
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of parental assessment of auditory skills in young children: a cross-sectional study in Italian language

Abstract: ObjectiveHearing impairments (HIs) that progress or have later onset may have specific effects on language and cognitive development, but are difficult to suspect during routine primary care visits. Family concern regarding hearing is thought to represent an important risk factor requiring audiological examination. Yet it is not clear how successful parents are in recognising the consequences or specific suspect elements of HI in young children. The aim of this study is to verify whether parents of at-risk chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… Primary schools, South Africa hearScreen smartphone screening app and conventional screening audiometry Diagnostic audiometry - No significant difference in performance - Smartphone screener and conventional screening demonstrated equivalent sensitivity (75%) and similar specificity (98.5% and 97% respectively) - Positive and negative predictive values 52.9% and 99.4% for smartphone screener, and 36.7% and 99.4% for conventional hearing screening. - No confidence intervals reported Ramkumar et al 2018 [ 47 ] Non-randomised comparative study 119 children (43) and young infants (76) aged 0-5 years Trained village health workers, community setting, India Distortion Product Otoacoustic Emissions (DPOAE) Tele-Auditory Brainstem Response testing - The study found acceptable validity: sensitivity of DPOAE screening was 75% (CI: 69-81) and specificity, 91% (CI: 87-95) - Negative and positive predictive values were 99% (CI: 98-100) and 27% (CI: 21-33), respectively Mealings et al, 2020 [ 44 ] Non-randomised comparative study 297 Aboriginal and Torres Strait Islander children aged 4–14 years Primary schools, Australia Sound Scouts game-based hearing test app for smartphones and tablets Pure tone audiometry, Listening in Spatialised Noise – Sentences high-cue condition - Sensitivity of Sound Scouts for average hearing loss of >20 dB HL was 41% and specificity was 89%; and for average hearing loss >30 dB HL, sensitivity at 88% and specificity at 88% - Consistent pass/fail results on Sound Scouts speech-in-noise measure and Listening in Spatialised Noise – Sentences test high-cue condition were found for 73% of children Orzan et al 2021 [ 53 ] Non-randomised comparative study 309 children aged 1-36 months Oto-rhino-laryngology and audiology unit of a medical institute, Italy Parental assessment of auditory skills using the Questionnaire on Hearing and Communication Abilities (QUAC) Audiological evaluation of children at a secondary care institute - Parents reported a decrease in auditory skills for children with sensorineural hearing loss (Χ 2 (2)=14.4, p =0.003), with increased concern expressed in 59% compared with 24% in normally hearing children - Positive predictive value was 0.78, but with low sensitivity (0.39) - No confidence intervals reported - Conclusion: parents have capacity to recognise non-typical audito...…”
Section: Resultsmentioning
confidence: 95%
“… Primary schools, South Africa hearScreen smartphone screening app and conventional screening audiometry Diagnostic audiometry - No significant difference in performance - Smartphone screener and conventional screening demonstrated equivalent sensitivity (75%) and similar specificity (98.5% and 97% respectively) - Positive and negative predictive values 52.9% and 99.4% for smartphone screener, and 36.7% and 99.4% for conventional hearing screening. - No confidence intervals reported Ramkumar et al 2018 [ 47 ] Non-randomised comparative study 119 children (43) and young infants (76) aged 0-5 years Trained village health workers, community setting, India Distortion Product Otoacoustic Emissions (DPOAE) Tele-Auditory Brainstem Response testing - The study found acceptable validity: sensitivity of DPOAE screening was 75% (CI: 69-81) and specificity, 91% (CI: 87-95) - Negative and positive predictive values were 99% (CI: 98-100) and 27% (CI: 21-33), respectively Mealings et al, 2020 [ 44 ] Non-randomised comparative study 297 Aboriginal and Torres Strait Islander children aged 4–14 years Primary schools, Australia Sound Scouts game-based hearing test app for smartphones and tablets Pure tone audiometry, Listening in Spatialised Noise – Sentences high-cue condition - Sensitivity of Sound Scouts for average hearing loss of >20 dB HL was 41% and specificity was 89%; and for average hearing loss >30 dB HL, sensitivity at 88% and specificity at 88% - Consistent pass/fail results on Sound Scouts speech-in-noise measure and Listening in Spatialised Noise – Sentences test high-cue condition were found for 73% of children Orzan et al 2021 [ 53 ] Non-randomised comparative study 309 children aged 1-36 months Oto-rhino-laryngology and audiology unit of a medical institute, Italy Parental assessment of auditory skills using the Questionnaire on Hearing and Communication Abilities (QUAC) Audiological evaluation of children at a secondary care institute - Parents reported a decrease in auditory skills for children with sensorineural hearing loss (Χ 2 (2)=14.4, p =0.003), with increased concern expressed in 59% compared with 24% in normally hearing children - Positive predictive value was 0.78, but with low sensitivity (0.39) - No confidence intervals reported - Conclusion: parents have capacity to recognise non-typical audito...…”
Section: Resultsmentioning
confidence: 95%
“…Listening skills checklists vary considerably in their ability to correctly identify current hearing loss (sensitivity, 100% and 39%) and to correctly identify no current hearing loss (specificity, 75% and 93%), with positive predictive values of 7% and 78%. 38,39 A listening skills questionnaire developed for Aboriginal and Torres Strait Islander children reported normative data, but lacked information on sensitivity, specificity, and positive predictive values. 40 Very low overall certainty of evidence may relate to the emergent nature of listening skills checklists in EHHCs.…”
Section: Summary Of Evidencementioning
confidence: 99%